Worldviews education : strengthening social inclusion - Halafoff, Anna (2022)
Growing clashes within cultures, and the ongoing threat of terrorism, have drawn attention to the importance of educating youth about different worldviews – religious, spiritual and non-religious – as a strategy to prevent violent extremism and to create socially inclusive and peaceful societies.